Cardiovascular Damage Associated With Chest Irradiation - Mrotzek, Simone M.; Rassaf, Tienush; Totzeck, Matthias (Frontiers in Cardiovascular Medicine, 2020)
The improvement of anticancer-therapies results in a greater amount of long-term survivors after radiotherapy. Therefore, the understanding of cardiotoxicity after irradiation is of increasing importance. Cardiovascular adverse events after chest irradiation have been acknowledged for a long time but remain difficult to diagnose. Long-term cardiovascular adverse events may become evident years or decades after radiotherapy and the spectrum of potential cardiovascular side effects is large. Recent experimental and clinical data indicate that cardiovascular symptoms may be caused especially by heart failure with preserved ejection fraction, which remains incompletely understood in patients after radiation therapy. Heart radiation dose and co-existing cardiovascular risk factors represent some of the most important contributors for incidence and severity of radiation-induced cardiovascular side effects. In this review, we aim to elucidate the underlying patho-mechanisms and to characterize the development of radiation-induced cardiovascular damage. Additionally, approaches for clinical management and treatment options are presented.